Epilepsy in adulthood: Prevalence, incidence, and associated antiepileptic drug use in autistic adults in a state Medicaid system. (April 2021) - Bishop, Lauren; McLean, Kiley J; Rubenstein, Eric
Although epilepsy commonly presents with autism in children, it is currently unknown whether established estimates represent the prevalence and incidence of epilepsy in autistic adults. Our objective was to use population-level Medicaid data to determine prevalence, incidence, and antiepileptic drug use associated with epilepsy in a unique population of autistic adults aged 21+ with (N = 2738) and without (N = 4775) intellectual disability and to compare results to adults with intellectual disability alone (N = 18, 429). We found that 34.6% of autistic adults with intellectual disability and 11.1% of autistic adults without intellectual disability had epilepsy, compared to 27.0% of adults with intellectual disability alone. New incidence of epilepsy was 23.6 incident cases per 1000 person years (95% confidence interval: 21.3, 26.2) in autistic adults with intellectual disability, 7.7 incident cases per 1000 person years (95% confidence interval: 6.6, 8.9) in autistic adults without intellectual disability, and 15.9 incident cases per 1000 person years (95% confidence interval: 15.2, 16.7) in adults with intellectual disability alone. Female sex and intellectual disability were associated with increased risk of prevalent and incident epilepsy in autistic adults. Findings underscore the importance of treating prevalent epilepsy and screening and preventing incident epilepsy in autistic adults as they age. Lay abstract: Epilepsy is more common in autistic children compared to children without autism, but we do not have good estimates of how many autistic adults have epilepsy. We used data from a full population of 7513 autistic adults who received Medicaid in Wisconsin to figure out the proportion of autistic adults who have epilepsy, as compared to 18, 429 adults with intellectual disability. We also wanted to assess how often epilepsy is first diagnosed in adulthood. Finally, we wanted to see whether antiepileptic drugs are being used to treat epilepsy in autistic adults. We found that 34.6% of autistic adults with intellectual disability and 11.1% of autistic adults without intellectual disability had epilepsy, compared to 27.0% of adults with intellectual disability alone. Autistic women and autistic adults with intellectual disability were more likely than autistic men and autistic adults without intellectual disability to have both previous and new diagnoses of epilepsy. Finally, we found that antiepileptic medications are commonly prescribed to autistic people who do not have epilepsy potentially to treat mental health conditions or behavior problems, and that antiepileptic medications are not always prescribed to autistic people with epilepsy even though they are indicated as a first-line epilepsy treatment. The findings of this study highlight the need to effectively treat and prevent epilepsy in autistic adults.